Anxiety, Anxiety - Ballenger, James C
Rapid Reference to Anxiety provides the reader with authoritative and accessible information from a clinical expert in the field, to assist with treatment decisions. The contain covers the diagnosis, prevention, treatment, and management of anxiety disorders. the book also provides standard core content (epidemiology - management/ therapy) combined with the additional information, such as FAQs and patient organisations, needed by the GP to provide effective patient care. It also includes drugs listings, clinical trials, information on future developments and web site listings to keep the reader up to speed with new developments and to extend their knowledge of the disease area